Pengaruh Kepemimpinan Kepala Sekolah dan Kinerja Guru terhadap Efektivitas Pelaksanaan Standar Pelayanan Minimal SMP di Kota Sukabumi - Ahmad Riyadi (LPPM Institut Nasional Laa Roiba Bogor, 2021)
Minimum Service Standard (MSS) for the implementation of elementary and secondary education schools is a technical specification as a benchmark of minimum services that must be done by the district / city government in organizing schooling activities in the field of primary and secondary education.A measure of the success of the performance of the national education system is the guarantee of education accountability, one of the indicators is the enactment of an effective quality assurance management system in education to protect the community. The purpose of this study is to find out: 1) The influence of the leadership of the principal on the effectiveness of the implementation of Minimum Service Standards (SPM) of junior high schools in Sukabumi City.2) Influence of teacher performance on the effectiveness of the implementation of Minimum Service Standards (MSS) of junior high schools in Sukabumi City.The method used in this study is quanttif, with the data analysis technique using inferential descriptive statics. The results of the study showed that the principal's leadership variable (X1) directly affects the effectiveness of the implementation of junior high school SPM in Sukabumi City by 4.5%, and indirectly (through teacher performance) by 1.6%.While the influence of teacher performance (X2) on the effectiveness of junior high school implementation in Sukabumi City by 15.4%.Therefore, it can be concluded that 1) There is an influence between the leadership of the principal on the effectiveness of the implementation of junior high school in Sukabumi City.2) There is an influence between the performance of teachers on the effectiveness of the implementation of junior high school in Sukabumi City.3) There is the influence of the principal's leadership and teacher performance together on the effectiveness of the implementation of Minimum Service Standards (MSS) of junior high schools in Sukabumi City.